Climate variability in the northern Mediterranean across the onset of the Messinian salinity crisis: insights from inorganic and organic geochemical proxies - Mathia Sabino; Enno Schefuß; Marcello Natalicchio; Francesco Dela Pierre; Daniel Birgel; David Bortels; Bernhard Schnetger; Jörn Peckmann (PANGAEA, 2020)
This data set was used to trace the climate and hydrologic variability in the northern Mediterranean in the late Miocene, from about 6.07 to 5.92 Ma. This time interval encompasses the onset (5.97 Ma) of the Messinian salinity crisis (MSC), an event which lead to prominent environmental changes in the Mediterranean area. The Messinian organic-rich shales and marls are cropping out in the Govone section (44°48'08''N; 8°07'34''E, NW Italy). The analyses included X-ray fluorescence (XRF), lipid biomarkers and their compound specific carbon and hydrogen stable isotopes. XRF was done to assess the distribution of major (Al, Si, Ti) and trace (Zr) elements. Si/Al, Ti/Al and Zr/Al ratios were used to qualitatively assess the influence of aeolian inputs. Lipid biomarker analyses targeted long-chain n-alkanes, derived from leaf waxes of land plants, which were identified and quantified, allowing to trace terrestrial organic matter input in the study area. We calculated the Carbon Preference Index (Bryan and Evans, 1961) based on the concentration of the n-C24 to n-C34 alkanes to trace the level of degradation/contamination of the terrestrial organic matter. Finally, carbon (δ13C) and hydrogen (δ2H) stable isotopes of the n-C31 and n-C33 alkanes were determined. δ13C values allowed to reconstruct variations in vegetation (C3 vs C4 plants), while δ2H values helped in reconstructing the hydrological cycle at the onset of the Messinian salinity crisis in the northern Mediterranean. Bray, E.E., Evans, E.D., 1961. Geochimica and Cosmochimica Acta 22, 2–15. https://doi.org/10.1016/0016-7037(61)90069-2